Social capital: A double-edged sword - Harold L. Cole; Dirk Krueger; George J. Mailath; Yena Park (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We analyze efficient risk-sharing arrangements when coalitions may deviate. Coalitions form to insure against idiosyncratic income risk. Self-enforcing contracts for both the original coalition and any deviating coalition rely on a belief in future cooperation which we term capital". We treat the contracting conditions of original and deviating coalitions symmetrically and show that higher social capital tightens incentive constraints since it facilitates both the formation of the original as well as a deviating coalition. As a consequence, although social capital facilitates the initial formation of coalitions, the extent of risk sharing in successfully formed coalitions is declining in the extent of social capital and equilibrium allocations might feature resource burning or utility burning: social capital is indeed a double-edged sword.
Keywords: E21; G22; D11; D91; 330; Financial Coalition; Limited Enforcement; Risk Sharing; Coalition-Proof Equilibrium